Assessment of Risk of Malignancy and Concordance in Salivary Gland Cytopathology Using the Milan System of Reporting, with Emphasis on Angiogenesis - Pranita Mohanty; Sonali Kar; Surabhi Singh (Hail Journal of Health Sciences)
Background: Salivary gland lesions comprise a broad range of both neoplastic and non-neoplastic conditions, and most of them can be diagnosed by cytology. However, varied ways of reporting sometimes put clinicians on edge, and treatment gets delayed. Aim: Hence, “The Milan System for Reporting Salivary Gland Cytopathology” (MSRSGC) was introduced and followed by many cytopathologists to give an uniform reporting pattern, thus guiding clinicians to render prompt and better treatment. Also, we performed CD34 immunohistochemistry (IHC) to evaluate significant differences in microvessel density (MVD) in benign and malignant salivary tumors. Here, we analyzed a total of 469 fine needle aspiration cytology (FNAC) cases, among whom 323 (68.9%) were corroborated with histopathological study. Materials and Methods: All the salivary gland swelling cases presented to the surgical departments of our institute and underwent FNAC. Cytosmears were routinely stained with diff quik and H and E stain and reported as per MSRSGC. Follow-up histopathology could be done only in 68.9% cases, and CD34 IHC is done in tumor cases only to differentiate between benign and malignant tumors. Results: A total of 469 FNAC of salivary swelling cases were analyzed, and 323 (68.9%) cases were correlated with histopathology. The mean age of the patients was 37.2 years, with male predominance. Majority of the lesions were in the parotid gland (42%). MSRSGC category II (non-neoplastic) was the most common category (52%). The analysis showed a positive predictive value, negative predictive value, sensitivity, specificity, and accuracy of 93%, 90%, 66.3%, 98.4%, and 90.4%, respectively. Out of total 91 tumor cases, MVD was found to be higher in malignant tumors, lower in benign tumors, highest in mucoepidermoid carcinoma, and lowest in sialadenosis with significant P = 0.000. Conclusion: Reporting of the salivary gland cytology using the six-tiered Milan system is a reliable and cost-effective method and offers a standardized framework for categorizing salivary gland lesions, assessing the risk of malignancy (ROM) and a guide therapeutic approach. Along with evaluation of MVD by CD34 IHC, a potential biomarker for tumor angiogenesis also aids the assessment of ROM.